Qifu Huazhuo formula for gout recurrence prevention: an interim analysis combining clinical outcomes with proteomic and metabolomic profiling - Shen, Zhengdong; Zhu, Fangjie; Chu, Yongliang; Wang, Haiyu; Wang, Maojie; Chen, Xiumin; Xiao, Yunting; Yang, Yongqiang; Huang, Runyue (Frontiers in Pharmacology, 2025)
PurposeGout is a chronic disease caused by the deposition of monosodium urate crystals in joints and tissues. The Qifu Huazhuo (QFHZ) Formula has shown effectiveness and safety in the management of gout. However, the role of QFHZ in the mitigation of gout needs to be further explored.Materials and methodsUHPLC-MS/MS was used to identify potential metabolites of QFHZ. Then we conducted a midpoint evaluation of the clinical study on the treatment of gout with QFHZ formula. The clinical study was a monocenter, open-label, randomized controlled trial. Eligible participants were allocated to TM, WM and TWM three groups in random. Participants in TM, WM and TWM group were received QFHZ (250 mL/dose, twice daily, oral), febuxostat (40 mg/dose, once daily, oral) and combination of febuxostat (40 mg/dose, once daily, oral) with QFHZ (250 mL/dose, twice daily, oral) for 12 weeks respectively. The primary efficacy endpoint is the percentage change in serum uric acid. The secondary efficacy endpoint include frequency of gout attacks, the change in estimated glomerular filtration rate (eGRF) and serum creatinine from baseline. Proteomic and metabolomic profiling was performed on paired pre- and post-treatment plasma samples.ResultsPharmacological studies have indicated that QFHZ contains 14 major metabolites. Clinical research has found that, TM can reduce the frequency of gout attacks compared to WM (p = 0.0006), while no significant differences were observed in the percentage change of serum uric acid levels across the three groups. Combined with proteomics and metabolomics analysis, it was discovered that QFHZ may regulate neutrophil extracellular trap (NET) formation, complement, lysosomes, phagosomes, and ferroptosis related biomolecules.ConclusionQFHZ shows distinct advantages in preventing gout recurrence over urate-lowering therapy alone, with multi-omics profiling revealing its potential multi-target effects. Future studies should validate these findings in larger cohorts and further elucidate the underlying molecular mechanisms.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=198890, identifier ChiCTR2300073188.